Формування продуктивності інтродукованого в центральній частині України Panicum virgatum L. (проса лозоподібного) - Кулик, М.І.; Юрченко, С.О. (Фактори експериментальної еволюції організмів, 2014)
Aims. To use plant phytomass for biofuels production peculiarities formation phytomass yield and productivity of seeds a new, exotic culture – switchgrass. Methods. Research Methods in the field experiments – conventional and special: quantitative indicators of plant. Results. The results of the three-year research: the duration of the growing season, forming the elements of the vegetative and generative performance culture Panicum virgatum L. when grown sorts of American origin introduced in the central steppes of Ukraine. Conclusions. Is established elements of the structure part (height and number of plants per unit area), dry phytomass yield and seed production the switchgrass. Stated that switchgrass well acclimatized to growing conditions in centralUkraine and can be used as feedstock for biofuel production plant origin.